Analysis of sound level emitted by vehicle regarding age. (November 2017) - Sancho, S.; Gaja, E.; Peral-Orts, R.; Clemente, G.; Sanz, J.; Velasco-Sánchez, E.
Highlights: Almost 6 million noise measurements have been managed to assess the sound effect of mechanical wear of vehicles. A light increase of noise emission due to vehicles' aging has been detected. It has been estimated at around 0.02 dB per year for the fleet as a whole. The sound effect with the age in the vehicle fleet can be included on traffic noise prediction models to be used in noise maps. Abstract: Traditionally, road traffic has been considered the main noise source in urban and interurban areas. As a consequence, governments have developed some new regulations to assess and control these constantly growing noise sources[1] . At the same time, numerous research groups have analysed and studied the main characteristics of new models of vehicles as a noise source and how technological improvements can reduce the overall levels emitted by road traffic, considered as a linear source. However, the sound effect of mechanical wear of vehicles has not been deeply studied, neither analysed. This paper aims to analyse the evolution of noise emissions of different vehicle types over time, based on the results of real technical inspections of vehicles. Since August 2004, the Technical Inspection of Vehicles Centres (ITVs) located in the Valencian Region have been recording the noise emissions levels of millions of vehicles in static tests, in accordance with Decree 19/2004[2] passed by the Consell de la Generalitat (Regional Council). This extensive data logging provides a great opportunity to evaluate sound characteristics of the vehicles of this region over the last 7 years. Therefore, in this paper, sound trend of different types of vehicles depending on the passing of the years is analysed. The purpose of this study is to determine the evolution of the sound level of vehicles over time and the influence on traffic noise prediction models used to develop noise maps.